Analysis of effects of moving wall direction in a one sided semi-circular porous cavity on mixed magneto-bioconvection in the presence of hybrid nanofluid with oxytactic bacteria - Hussain, Shafqat; Öztop, Hakan Fehmi; Aly, Abdelraheem M.; Abu-Hamdeh, Nidal H. (Elsevier, 2023)
A computational analysis on the effects of direction of wall movement in a one sided semi-circular porous cavity on mixed magneto-bioconvection of hybrid nanofluid in the presence of oxytactic bacteria has been performed. The working fluid is the hybrid nanofluid. The enclosure is cooled from semi-circle side and heated from moving lid under the effect of uniform magnetic field in the horizontal direction. The numerical solution of governing equations is obtained by using the higher order finite element method (FEM). The reliability of designed solver is tested through the experimental and numerical data available in the literature. Two cases of the boundary conditions are considered related to the tendency of right vertical lid of the cavity. Other parameters are Richardson number, Darcy number, Hartmann number, Peclet number and porosity. It is found that moving lid direction is the most effective parameter for the flow field, isotherms, oxygen and microorganism distributions. Moreover, higher heat transfer rate is obtained in Case-I for different values of Darcy number. Around 10% increment is occurred on mass transfer with different Pe number in case of downward moving lid due to increment of convection mode of heat transfer inside the cavity.
Keywords: Heat transfer; Thermal bioconvection; MHD mixed convection; Oxygen; Semi-circular lid-driven cavity